(untitled) (Journal of the College of Basic Education, 2022)
There is an undeniable fact, which is that the image of women continued to find its way to the poet’s giving, so it occupied its own space among his models through the ages of poetic giving, because it is the almost only outlet for clarifying the pledge of allegiance to the poetry of the world of women, which seemed an inspirational stimulus, which does not constitute the material of a poetic experience except when it transforms An inspiration that blinks the soul, so the saying turns around, and makes the woman a party that achieves his objective presence through a daily experience that the poet goes through, and here the woman entered the world of poetry, as a mother, wife, daughter, and lover, like any human element involved in making the event or influential in its applied course. There is spinning that lives the real human experience And there are lyrical stanzas in which the image of women did not go beyond the framework of the human element involved in making the special event in the poetic experience, and based on this, I have chosen the subject of my research, which is titled ((Andalusian ghazal poetry brides in the fifth and sixth centuries AH)), explaining the role of women. Her image and position in the poetic model took over the poetry of Andalusian poets during that period, embodying her ability to represent the suffering of the Andalusian poet from the disintegration of all human and emotional relationships, which he felt were rapidly forming. On the one hand, or difficult to obtain on the other hand, and the image of the late beloved and recording the moment of her farewell, depicting the momentum of psychological excitement, and this is done by referring to the collections of Andalusian spinning poets, such as Ibn Zaydun, Al-Mutamid Ibn Abbad, Ibn Al-Labbana, Ibn Al-Haddad, Ibn Ammar, and Ibn Daraj Al-Qastly, and Ibn Hamdis, and what resulted from the results, we will list them in the conclusion of the research.